2021
DOI: 10.3390/jcm10143044
|View full text |Cite
|
Sign up to set email alerts
|

Grip Strength Correlates with Mental Health and Quality of Life after Critical Care: A Retrospective Study in a Post-Intensive Care Syndrome Clinic

Abstract: Post-intensive care syndrome (PICS) is characterized by several prolonged symptoms after critical care, including physical and cognitive dysfunctions as well as mental illness. In clinical practice, the long-term follow-up of PICS is initiated after patients have been discharged from the intensive care unit, and one of the approaches used is a PICS clinic. Although physical dysfunction and mental illness often present in combination, they have not yet been examined in detail in PICS patients. Grip strength is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(52 citation statements)
references
References 32 publications
1
51
0
Order By: Relevance
“…Muscle strength was also independently correlated with mental status and HRQOL [60], while muscle weakness seemed to contribute to the cognitive and mental sequelae in PICS (Figure 1). There is no therapeutic intervention of proven efficacy for PICS-related muscle weakness; however, several interventions have been assessed for prevention and symptom management and are under investigation [51,61,62].…”
Section: Physical Dysfunctionmentioning
confidence: 97%
See 3 more Smart Citations
“…Muscle strength was also independently correlated with mental status and HRQOL [60], while muscle weakness seemed to contribute to the cognitive and mental sequelae in PICS (Figure 1). There is no therapeutic intervention of proven efficacy for PICS-related muscle weakness; however, several interventions have been assessed for prevention and symptom management and are under investigation [51,61,62].…”
Section: Physical Dysfunctionmentioning
confidence: 97%
“…Physical dysfunction requires a multidisciplinary approach that includes exercise, physiotherapy, occupational therapy, and rehabilitation and requires the involvement of critical care physicians, neuropsychiatrists, physiotherapists, and respiratory therapists (Figure 4) [154]. New promising techniques that target recovery from PICS by combining objective lean body mass and metabolic assessments, novel nutrition and exercise inter-ventions can be applied in this setting [53,60,61]. For example, it has been shown that muscle glycogen stores are depleted early during critical illness [60].…”
Section: Pics Prevention and Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The MRC score is mainly used to diagnose ICU-AW, but it can be feasible to follow the physical functional effects of PICS [29]. The grip strength is also valid to evaluate muscle strength associated with mental health and QOL [30]. The 6-min walk test is one of the most reliable physical functional tests in PICS although this is feasible in a limited number of patients [9,28].…”
Section: Pics-fmentioning
confidence: 99%